2013
DOI: 10.1136/gutjnl-2012-304219
|View full text |Cite
|
Sign up to set email alerts
|

Hypomethylation of long interspersed nuclear element-1 (LINE-1) leads to activation of proto-oncogenes in human colorectal cancer metastasis

Abstract: Objective Hypomethylation of LINE-1 elements has emerged as a distinguishing feature in human cancers. Limited evidence indicates that some LINE-1 elements encode an additional internal antisense promoter, and increased hypomethylation of this region may lead to inadvertent activation of evolutionarily methylation-silenced downstream genes. However, the significance of this fundamental epigenetic mechanism in colorectal cancer (CRC) has not been investigated previously. Design We analysed tissue specimens fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
207
0
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 252 publications
(220 citation statements)
references
References 50 publications
8
207
0
5
Order By: Relevance
“…L1 expression correlates with tumorigenesis in some cancers and may contribute to the process of transformation in a minority of cases. Moreover, previous studies 32,33,35,37,38 in a small number of cancer types have shown that L1 activity and expression differ among and within cancer types and may fluctuate during cancer evolution, suggesting its potential as a cancer biomarker. Future study is still required to illustrate why L1 activity and expression are deregulated in cancer and how they contribute to tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…L1 expression correlates with tumorigenesis in some cancers and may contribute to the process of transformation in a minority of cases. Moreover, previous studies 32,33,35,37,38 in a small number of cancer types have shown that L1 activity and expression differ among and within cancer types and may fluctuate during cancer evolution, suggesting its potential as a cancer biomarker. Future study is still required to illustrate why L1 activity and expression are deregulated in cancer and how they contribute to tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In CRC and HCC, L1 insertion into the intronic region of MET (L1-MET) leads to elevated expression of MET. 38,46 In CRC and associated liver metastasis tissue, the hypomethylation of L1 ASP within L1-MET is correlated with elevated MET expression. 38 In HCC, L1-MET was also identified and its hypomethylation was found to be correlated with elevated c-MET expression.…”
Section: Functions Of L1s In Cancer Retrotransposition-dependent Funcmentioning
confidence: 99%
See 3 more Smart Citations